Environmental health nursing education: One school's journey. Issue 2 (28th September 2020) - McElroy, Katie G.; Gilden, Robyn; Sattler, Barbara
Abstract: Nurse educators have long recognized the need for an increased focus on environmental health education in nursing. For decades, schools of nursing have answered the call to action put forth by the Institute of Medicine and the American Nurses Association to incorporate environmental health content into nursing curricula. This article details the experiences of faculty and staff at the University of Maryland School of Nursing as they launched a national environmental health nursing organization, developed individual undergraduate elective courses on environmental health and climate change, and created a post‐baccalaureate certificate program. We also report student registration and evaluation data from five environmental health courses over 10 years. Five hundred five undergraduate and 291 graduate nursing students from a variety of programs received formal environmental health education. Relevance of content was consistently highly rated, ranging from 4.17 to 4.61 out of 5, and students completed projects on a wide range of environmental health topics. Graduates of the certificate program have greatly impacted their communities in the areas of nursing practice, education, and policy.